Robotic Microcapsule Assemblies with Adaptive Mobility for Targeted Treatment of Rugged Biological Microenvironments - Tran, Hong Huy; Xiang, Zhenting; Oh, Min Jun; Liu, Yuan; Ren, Zhi; Chen, Chider; Jaruchotiratanasakul, Nadasinee; Kikkawa, James M.; Lee, Daeyeon; Koo, Hyun; Steager, Edward (ACS nano, 2025)
Microrobots are poised to transform biomedicine by enabling precise, noninvasive procedures. However, current magnetic microrobots, composed of solid monolithic particles, present fundamental challenges in engineering intersubunit interactions, limiting their collective effectiveness in navigating irregular biological terrains and confined spaces. To address this, we design hierarchically assembled microrobots with multiaxis mobility and collective adaptability by engineering the potential magnetic interaction energy between subunits to create stable, self-reconfigurable structures capable of carrying and protecting cargo internally. Using double emulsion templates and magnetic control techniques, we confine 10 nm iron oxide and 15 nm silica nanoparticles within the shell of 100 μm microcapsules that form multiunit robotic collectives. Unexpectedly, we find that asymmetric localization of iron oxide nanoparticles in the microcapsules enhances the intercapsule potential energy, creating stable connections under rotating magnetic fields without altering the magnetic susceptibility. These robotic microcapsule collectives exhibit emergent behaviors, self-reconfiguring into kinematic chain-like structures to traverse complex obstacles, arched confinements, and adhesive, rugged biological tissues that typically impede microscale systems. By harnessing these functions, we demonstrate targeted antifungal delivery using a localized biofilm model on mucosal tissues, showing effective killing ofCandida without binding or causing physical damage to host cells. Our findings show how hierarchical assembly can produce cargo-carrying microrobots with collective, self-adaptive mobility for traversing complex biological environments, advancing targeted delivery for biomedical applications.